Active disassembly of devices and materials - Lin, Xiaocong (2014)
This report documents a general introduction to active disassembly of shape memory materials. This active disassembly uses the technology of shape memory effect and this will be shown during the active disassembly of Polylactic acid (PLA) and Hydrogel. Using the Differential Scanning Calorimeter (DSC) test, the training temperature can be obtained and the shape memory effect experiments can be conducted. The PLA experiment will simulate the use of shape memory materials in active disassembly of devices such as mobile phones and the Hydrogel experiment will show how shape memory materials can be disassembled within itself with two stimulus, water and heat. The various forms of active disassembly are very useful and can be implemented into real life applications which can benefit mankind.